Inorganic coating opening covering strip adhesive tape and preparation method thereof

Through the design of inorganic coating cover strip tape, the problem of damage and repair difficulty of traditional waterproof coils in cross-operation is solved, and efficient local repair and adhesive force is achieved, ensuring the continuity and reliability of the waterproof material.

CN119264826APending Publication Date: 2025-01-07KEJIAN POLYMER MATERIALS (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411507275.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional prepaved waterproof coils are easily damaged during cross-work, and are not easy to cut and repair due to width and weight limitations. The lack of effective coating cover strip tape is used for local repair and strengthening bonding areas, resulting in waterproofing materials. Continuity and reliability are impaired.

Method used

Using inorganic coating cover strip tape, including inorganic coating, first self-adhesive layer, embryonic body layer and second self-adhesive layer, chemical crosslinking is formed through aqueous inorganic coating and silane coupling agent to ensure the transparency of the coating and Adhesive force and hierarchical design using PET film and double-sided release paper.

Benefits of technology

It realizes the translucent appearance of the inorganic coating cover strip tape, with cold water resistance and chemical corrosion resistance, maintains efficient adhesion, avoids the hidden dangers of water seepage caused by traditional coating thickness, and enhances the local repair and sealing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264826A_ABST
    Figure CN119264826A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and provides an inorganic coating opening covering strip adhesive tape and a preparation method thereof. The inorganic coating opening covering strip adhesive tape comprises an inorganic coating, a first self-adhesive layer, a blank body layer and a second self-adhesive layer which are sequentially attached together. The inorganic coating is obtained by coating and drying a water-based inorganic coating; the water-based inorganic coating comprises the following components in parts by mass: 80-90 parts of water-based silicon dioxide dispersion; 0.5-1 part of a wetting agent; 5-10 parts of a solubilizer; 2-8 parts of a silane coupling agent; and 0.5-5 parts of a pH regulator. The inorganic coating is used as a main film forming substance, can prevent non-polar plasticizers such as white oil and polyisobutene of the self-adhesion layer from migrating to the polymer coating, and is not easy to generate surface adhesion; the inorganic coating, the silane coupling agent and other assistants assist in film forming to generate chemical crosslinking, cold water resistance can be achieved, silicon dioxide can be corroded and dissolved by sodium hydroxide or potassium hydroxide and other strong bases in post-pouring concrete, and hydrates of the post-pouring concrete can penetrate through the coating to make contact with the self-adhesive layer so as to maintain excellent adhesive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to an inorganic coating cover strip tape and a preparation method thereof. Background Art

[0002] Pre-laid waterproofing membranes are laid bare on the base layer. The overlapping operations and various types of work can easily cause physical damage to the membrane surface. Traditional pre-laid waterproofing membranes are often difficult to cut and repair due to their width and weight. There is a need to develop coated cover tapes for localized repairs of pre-laid waterproofing membranes, penetrating mechanical fixing and sealing, corner sealing, and overlap reinforcement sealing. These tapes can effectively repair damaged spots and strengthen weak localized bonding areas, ensuring the continuity and reliability of the waterproofing material.

[0003] CN220297995U discloses a repair tape with an organic-inorganic composite coating as a temporary protective layer. The organic-inorganic composite coating layer comprises a polymer coating layer and a granular layer stacked sequentially from top to bottom. The polymer coating layer is made of at least one of an acrylic polymer, polyvinyl acetate, polyethylene vinyl acetate copolymer, acrylate-styrene, acrylate-vinyl acetate, chloroprene rubber, butyl rubber, styrene-butadiene, and SEBS. The granular layer is made of at least one of partially hydrated cement, fully hydrated cement, calcium carbonate, silicate sand, river sand, amorphous silica, slag, alumina trihydrate, slate ash, granite ash, calcite, quartz, zeolite, vermiculite, bauxite, shale, feldspar, perlite, silicate, and aluminate. The particle size of the granular layer is 100 to 1000 μm. This coating is not transparent due to the large filler particle size. Moreover, in areas with thicker thickness, the silicate hydration layer cannot penetrate the coating and the self-adhesive layer to form an effective bond, resulting in a rapid decrease in adhesion and the risk of water seepage.

[0004] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the Invention

[0005] The present invention is made to solve the above problems, and its purpose is to provide an inorganic coating cover strip tape and a preparation method thereof.

[0006] The present invention provides an inorganic coating cover strip tape having the following characteristics:

[0007] The inorganic coating, the first self-adhesive layer, the embryonic layer and the second self-adhesive layer are sequentially laminated together;

[0008] Among them, the inorganic coating is obtained by coating and drying a water-based inorganic coating, and the water-based inorganic coating includes the following components in proportion by mass: water-based silica dispersion: 80-90 parts; wetting agent: 0.5-1 part; solubilizer: 5-10 parts; silane coupling agent: 2-8 parts; pH adjuster: 0.5-5 parts.

[0009] The inorganic coated cover strip tape provided by the present invention may also have the following characteristics: the aqueous silica dispersion is a silica sol with a particle size of 5nm to 100nm, the wetting agent is sodium salt of di-2-ethylhexyl succinate, and the solubilizer is a water-soluble solvent; the silane coupling agent is a silane containing two, three or four alkoxy groups, or a mixture of several thereof.

[0010] The inorganic coated cover strip tape provided by the present invention may also have the following characteristics: wherein the aqueous silica dispersion is Guangdong Huihe SW-40 acidic silica sol, the wetting agent is BASF's HYDROPALAT WE 3475, the solubilizer is ethanol, and the silane coupling agent is KH-550 aminopropyltriethoxysilane and / or KH-560 3-glycidyloxypropyltrimethoxysilane.

[0011] The inorganic coating cover strip adhesive tape provided by the present invention may also have the following feature: wherein the pH regulator is ammonia water with a concentration of 25%-28%.

[0012] The inorganic coating cover strip tape provided by the present invention may also have the following characteristics: wherein the materials of the first self-adhesive layer and the second self-adhesive layer are both silane-modified butyl self-adhesive containing white oil and polyisobutylene, and the embryonic layer is PET film.

[0013] The inorganic coating cover strip adhesive tape provided by the present invention may also have the following features: a release layer, wherein the release layer is bonded together with the second self-adhesive layer.

[0014] The inorganic coating cover strip tape provided by the present invention may also have the following feature: wherein the release layer is a release film or release paper.

[0015] The inorganic coating cover strip tape provided by the present invention may also have the following feature: wherein the release layer is a double-sided release paper.

[0016] The inorganic coated cover strip tape provided by the present invention may also have the following characteristics: the thickness of the inorganic coating is 0.03mm-0.2mm, the thickness of the first self-adhesive layer is 0.1mm-0.5mm, the thickness of the embryo layer is 0.05mm-0.2mm, the thickness of the second self-adhesive layer is 0.1mm-0.5mm, and the thickness of the release layer is 0.01mm-0.1mm.

[0017] The present invention also provides a method for preparing the inorganic coating cover strip tape, which has the following characteristics and comprises the following steps:

[0018] Step S1, adding an aqueous silica dispersion, a wetting agent, a solubilizer, and a silane coupling agent into a stirring tank, stirring and dispersing them uniformly; then adding a pH regulator, continuing stirring at room temperature for 0.5-1 hour to obtain a uniform emulsion dispersion, i.e., an aqueous inorganic coating, and discharging the material for later use;

[0019] Step S2, preparing silane-modified butyl rubber according to Example 1 in CN113621343B;

[0020] Step S3: Feed the silane-modified butyl rubber into an extruder, and extrude 0.2 mm to 0.4 mm thick butyl rubber layers onto both sides of the PET embryo at one time through an extrusion die to obtain a first self-adhesive layer and a second self-adhesive layer. The extrusion temperature is set between 80° C. and 110° C. The second self-adhesive layer is then composited with a double-sided release paper and rolled up to obtain a semi-finished product A.

[0021] Step S4, introduce the water-based inorganic coating obtained in step S1 into the glue tank, apply it on the first self-adhesive layer through a rubber roller, control the thickness of the dry glue to be 0.03mm-0.10mm, bake and dry in an oven, and then roll up to obtain a large roll of semi-finished product B. Finally, the semi-finished product B is rolled up by a slitting machine to obtain a finished small roll.

[0022] Functions and effects of the invention

[0023] The inorganic coating cover strip adhesive tape prepared by the present invention uses the inorganic coating as the main film-forming substance, and exhibits a translucent appearance after film formation. The natural properties of the inorganic coating can prevent non-polar plasticizers such as white oil and polyisobutylene in the self-adhesive layer from migrating to the polymer coating, and surface adhesion is not easy to occur. In addition, the inorganic coating and auxiliary agents such as silane coupling agents assist in chemical cross-linking after film formation, and are resistant to cold water. In addition, silicon dioxide can be corroded and dissolved by strong alkalis such as sodium hydroxide or potassium hydroxide in post-cast concrete, and the hydrate of the post-cast concrete can pass through the coating and contact the self-adhesive layer, thereby maintaining excellent bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the structure of the inorganic coating cover strip tape of the present invention;

[0025] Figure 2 The present invention is a schematic diagram of the process of preparing an inorganic coating cover strip tape. DETAILED DESCRIPTION

[0026] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the following is a detailed description of an inorganic coated cover strip tape and a preparation method thereof in conjunction with embodiments and drawings.

[0027] Unless otherwise specified, the raw materials used in the present invention were purchased through general commercial channels. All test standards not mentioned here are national standards.

[0028] Figure 1 It is a schematic structural diagram of the multi-inorganic coating cover strip tape of the present invention.

[0029] like Figure 1 As shown, the multi-layer composite fireproof membrane is a five-layer structure laminated together in sequence, which includes, from top to bottom, an inorganic coating L1, a first self-adhesive layer L2, a body layer L3, a second self-adhesive layer L4 and a release layer L5.

[0030] The thickness of the inorganic coating is 0.03 mm to 0.2 mm, preferably a silica transparent coating of 0.03 mm to 0.1 mm.

[0031] The thickness of the first self-adhesive layer is 0.1 mm to 0.5 mm, and the material is preferably silane-modified butyl self-adhesive adhesive, and the thickness is preferably 0.2 mm to 0.4 mm.

[0032] The thickness of the embryo body layer is 0.05 mm to 0.2 mm, and preferably a PET film with a thickness of 0.05 mm to 0.1 mm is used as the embryo body.

[0033] The thickness of the second self-adhesive layer is 0.1 mm to 0.5 mm, preferably 0.2 mm to 0.4 mm. The second self-adhesive layer is made of the same material as the first self-adhesive layer, and may have a different thickness, but preferably has the same thickness as the first self-adhesive layer.

[0034] The thickness of the release layer is 0.01mm-0.1mm. The release layer needs to be torn off when used. It is a release film or release paper, preferably a double-sided release paper with a thickness of 0.02mm-0.05mm.

[0035] The above-mentioned inorganic coating is obtained by coating and drying a water-based inorganic coating, and comprises the following components in parts by mass:

[0036] Aqueous silicon dioxide dispersion: 80-90 parts;

[0037] Wetting agent: 0.5-1 part;

[0038] Solubilizer: 5-10 parts;

[0039] Silane coupling agent: 2-8 parts;

[0040] pH regulator: 0.5-5 parts.

[0041] Among them, the water-based silica dispersion uses silica sol with a particle size of 5nm to 100nm. It is an alkali-soluble inorganic substance. After film formation, the appearance is transparent or translucent and it is resistant to cold water. For example, Guangdong Huihe SW-40 acidic silica sol with a particle size of 50nm to 60nm can be selected.

[0042] The wetting agent is an additive that can reduce surface tension, preferably di-2-ethylhexyl succinate sodium salt, such as BASF's HYDROPALAT WE 3475, a 75% solution of di-2-ethylhexyl succinate sodium salt. The solubilizer is a water-soluble solvent, such as ethanol.

[0043] Silane coupling agent, one of the silanes containing two, three or four alkoxy groups or a mixture thereof, such as KH-550 aminopropyltriethoxysilane, KH-560 3-glycidyloxypropyltrimethoxysilane.

[0044] The pH regulator is industrial-grade ammonia water with a concentration of 25%-28%. The self-adhesive layer is a silane-modified butyl self-adhesive prepared according to Example 1 in CN113621343B. The embryo is a PET film.

[0045] Figure 2 The present invention is a schematic diagram of the process of preparing an inorganic coating cover strip tape.

[0046] like Figure 2 As shown, the preparation of the inorganic coating cover strip tape includes the following steps:

[0047] Step S1, preparation of water-based inorganic coating: adding water-based silica dispersion, wetting agent, solubilizer, and silane coupling agent to a stirring tank 7, stirring and dispersing them uniformly; then adding a pH regulator, continuing stirring at room temperature for 0.5-1 hour to obtain a uniform emulsion dispersion, i.e., a water-based inorganic coating, and discharging the material for later use.

[0048] Step S2, preparation of self-adhesive layer: using a mixer 1, prepare silane-modified butyl rubber according to Example 1 in CN113621343B.

[0049] Step S3, Self-Adhesive Layer Coating: Silane-modified butyl rubber is fed into extruder 2. A 0.2mm-0.4mm thick butyl rubber layer is extruded simultaneously through the extrusion die onto both sides of the PET substrate unwound by the first unwinder 3 to form the first and second self-adhesive layers. The extrusion temperature is set between 80°C and 110°C. The second self-adhesive layer is then laminated with the double-sided release paper unwound by the second unwinder 4 via roller 5. The semi-finished product A is then wound up by the first winder 6. The water-based inorganic coating of step S4 is applied to semi-finished product A within 24 hours.

[0050] Step S4, water-based inorganic coating coating, winding and slitting: the water-based inorganic coating obtained in step S1 is introduced into the glue tank, and is coated on the first self-adhesive layer of the semi-finished product A unwound by the third unwinder 8 by the glue roller of the roller coater 9, and the thickness of the dry glue is controlled to be 0.03mm-0.10mm. After being baked and dried in the oven 10, it is wound by the second winder 11 to obtain a large roll of semi-finished product B. The semi-finished product B is finally slit by the slitting machine 12, and then wound by the third winder 13 to obtain a finished small roll.

[0051] The materials used in the preparation examples, embodiments and comparative examples of the present invention are as follows:

[0052] Water: Deionized water product;

[0053] pH regulator: Ammonia (26%): industrial grade ammonia, concentration 26%;

[0054] Wetting agent: BASF's HYDROPALAT WE 3475, succinic acid di-2-ethylhexyl sodium salt 75% solution;

[0055] Water-based silica dispersion: Guangdong Huihe Company SW-40 acidic silica sol, nano-scale silica sol, particle size 50nm-60nm;

[0056] Solubilizer: ethanol, industrial grade alcohol;

[0057] Silane coupling agent: KH-550, Hangzhou Jessica Chemical, aminopropyltriethoxysilane, industrial grade; KH-560, Hangzhou Jessica Chemical, 3-glycidyloxypropyltrimethoxysilane, industrial grade;

[0058] Fumed silica: Cabot CAB-O-SIL LM-150 fumed silica;

[0059] Precipitated silica: Taicang Xinhong Chemical XH-201F ultrafine precipitated silica;

[0060] M4000 silicon micropowder: Lianyungang Changtong silicon micropowder M4000, 2000 mesh;

[0061] GCC 1158: Shanghai Hangchi heavy calcium carbonate, 1200 mesh;

[0062] Dispersant Archor D6601: Shanghai Weiyong Industrial, polyacrylate dispersant, effective content 41%.

[0063] Preparation Example 1:

[0064] This preparation example prepares a water-based inorganic coating, and the weight parts are as follows (total weight 600 kg):

[0065] SW-40 acidic silica sol: 87.5 parts;

[0066] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0067] Ethanol: 6 parts;

[0068] KH-560: 5 parts;

[0069] Ammonia water (26%): 1 part.

[0070] The preparation method is as follows: add SW-40 acidic silica sol, wetting agent, ethanol, and silane coupling agent into a stirring kettle, stir and disperse evenly; add ammonia water, continue stirring at room temperature for 0.5 hours to obtain a uniform emulsion dispersion, and discharge the material for standby use.

[0071] Preparation Example 2:

[0072] This preparation example prepares a water-based inorganic coating, and the weight parts are as follows (total weight 600 kg):

[0073] SW-40 acidic silica sol: 88 parts;

[0074] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0075] KH-550: 5 parts;

[0076] Ethanol: 6 parts;

[0077] Ammonia water (26%): 0.5 parts.

[0078] The preparation method is the same as that of Preparation Example 1.

[0079] Preparation Example 3:

[0080] This preparation example prepares a water-based inorganic coating, and the weight parts are as follows (total weight 600 kg):

[0081] SW-40 acidic silica sol: 88 parts;

[0082] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0083] KH-560: 2.5 parts;

[0084] KH-550: 2.5 parts;

[0085] Ethanol: 6 parts;

[0086] Ammonia water (26%): 0.5 parts.

[0087] The preparation method is the same as that of Preparation Example 1.

[0088] Preparation Example 4:

[0089] This preparation example prepares butyl rubber, which is prepared according to Example 1 of CN113621343B. The butyl rubber contains ingredients such as white oil and polyisobutylene.

[0090] Comparative Preparation Example 1:

[0091] Water: 67 parts;

[0092] Ammonia water (26%): 1 part;

[0093] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0094] KH-560: 5 parts;

[0095] Ethanol: 6 parts;

[0096] CAB-O-SIL LM-150 fumed silica: 20 parts;

[0097] Dispersant Archor D6601: 0.5 parts;

[0098] Preparation process: Add water, wetting agent, ethanol, silane coupling agent, and CAB-O-SIL LM-150 fumed silica to a stirred tank, stir at high speed until uniform dispersion is achieved, then add ammonia water and continue stirring at high speed for 0.5 hours to obtain a uniform emulsion dispersion. Discharge the material for later use.

[0099] Comparative Preparation Example 2:

[0100] CAB-O-SIL LM-150 fumed silica was replaced with XH-201F precipitated silica, and the other ingredients and process were the same as those in Comparative Preparation Example 1.

[0101] Comparative Preparation Example 3:

[0102] Water: 52 parts;

[0103] Ammonia water (26%): 1 part;

[0104] Wetting agent HYDROPALAT WE 3475: 0.5 parts;

[0105] KH-560: 5 parts;

[0106] Ethanol: 6 parts;

[0107] M4000 silicon micropowder: 35 parts;

[0108] Dispersant Archor D6601: 0.5 parts.

[0109] Preparation process: Add water, wetting agent, ethanol, silane coupling agent, and M4000 silicon micropowder into a stirring tank, stir at high speed to disperse evenly, then add ammonia water, continue stirring at high speed for 0.5 hours to obtain a uniform emulsion dispersion, and discharge the material for later use.

[0110] Comparative Preparation Example 4:

[0111] M4000 silicon micropowder was replaced by heavy calcium GCC 1158, and other ingredients and process were the same as those in Comparative Preparation Example 3.

[0112] Comparative Preparation Example 5:

[0113] SBC hot melt pressure sensitive adhesive was prepared according to comparative example 3 of CN117050698A.

[0114] Test Example 1:

[0115] This test example tests the basic properties of the water-based inorganic coatings of Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 4. The results are shown in Table 1. The test method is as follows:

[0116] Appearance: visual inspection;

[0117] Viscosity -23℃: tested according to GB / T 2794-2013 method;

[0118] Solid content: tested according to GB / T2793-1995 method;

[0119] Roller coating operability: Observe whether there is skinning or coating leakage when the paint is rolled.

[0120] Table 1 Basic properties of waterborne inorganic coatings of Preparation Examples 1 to 3 and Comparative Preparation Examples 1 to 4

[0121]

[0122] Examples and Comparative Examples:

[0123] The compositions of the tapes of Examples 1-3 and Comparative Examples 1-5 are shown in Table 2.

[0124] The preparation methods of the adhesive tapes of Examples 1-3 and Comparative Examples 1-4 are as follows:

[0125] The butyl rubber coating of Preparation Example 4 was fed into an extruder (extrusion temperature at 80°C) and extruded through an extrusion die at once to form a 0.3 mm (thickness see Table 2) butyl rubber layer on both sides of the PET embryo to obtain a first self-adhesive layer and a second self-adhesive layer (the second and fourth layers). The second self-adhesive layer was then composited with a double-sided release paper (the fifth layer) and rolled up to obtain a semi-finished product A. Within 24 hours of the preparation of the above semi-finished product A, the water-based inorganic coating obtained in Preparation Examples 1-3 and Comparative Preparation Examples 1-4 was introduced into a glue tank and coated on the first self-adhesive layer using a rubber roller. The dry glue thickness was controlled to be 0.05 mm. After drying in an oven, the semi-finished product B was rolled up to obtain a large roll. The semi-finished product B was finally rolled up on a slitting machine to obtain a small finished roll.

[0126] Comparative Example 5:

[0127] The SBC hot melt adhesive obtained in Comparative Preparation Example 5 was fed into the hot melt adhesive cylinder of the coating machine. The cylinder / hose / coating head temperature was set to 180°C, and the thickness was controlled to 0.15 mm. The adhesive was then applied simultaneously to both sides of the third PET embryo using a double-end slot coating die to form the second and fourth self-adhesive layers. The fourth and fifth layers of double-sided release paper were then combined and rolled to form semi-finished product A. All other aspects were the same as in Example 1.

[0128] Table 2. Composition of Examples and Comparative Examples

[0129]

[0130] Test Example 2

[0131] This test example tests the properties of the adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-5. The results are shown in Table 3. The test method is as follows:

[0132] Coating appearance (after drying): Visually observe whether the coating is transparent after drying;

[0133] Cold water resistance: After the tape is soaked in 23°C water for 7 days, rinse the coating with tap water for 1 minute and dry it at room temperature for 3 days. Touch the surface with your hand to see if it is sticky.

[0134] Adhesion: Store at 70℃ for 7 days, then cool to room temperature for 24 hours. Touch with hands to see if there is any adhesion. Peel strength with post-cast concrete: Test according to Section 6.20 of GB / T23457-2017.

[0135] Table 3. Performance comparison of examples and comparative examples

[0136]

[0137] As can be seen from Table 3, Examples 1-3 are all resistant to cold water (non-sticky) and have a translucent appearance after film formation. However, the films of Comparative Examples 1, 2, and 3 are white and opaque after film formation. However, because they are all made of silica, they can be corroded and dissolved by the alkalinity of concrete. The hydration layer of the concrete eventually penetrates the coating and self-adhesive layer to form an effective bond, and the peel force is greater than 1.5 N / mm.

[0138] Since calcium carbonate was used as the inorganic coating or SBC hot-melt adhesive as the self-adhesive layer in Comparative Examples 4 and 5, both exhibited insufficient cold water resistance and exhibited stickiness after drying. This indirectly suggests that chemical bonding between the silica coating and the silane-modified butyl self-adhesive layer in Examples 1, 2, and 3 and Comparative Examples 1, 2, and 3 provides cold water resistance, whereas chemical interfacial bonding cannot be achieved when calcium carbonate is used as the filler or SBC hot-melt adhesive is used as the self-adhesive layer. Furthermore, the peel strength is significantly reduced when calcium carbonate is used as the filler. This stickiness can easily cause workers to stick to their shoe soles, hindering construction.

[0139] The above embodiments are preferred examples of the present invention and are not intended to limit the scope of protection of the present invention.

Claims

1. An inorganic coating cover tape, characterized in that: include: The inorganic coating, the first self-adhesive layer, the embryo layer and the second self-adhesive layer are sequentially laminated together; Wherein, the inorganic coating is obtained by coating and drying a water-based inorganic coating, and the water-based inorganic coating comprises the following components in proportion by mass: Aqueous silicon dioxide dispersion: 80-90 parts; Wetting agent: 0.5-1 part; Solubilizer: 5-10 parts; Silane coupling agent: 2-8 parts; pH adjuster: 0.5-5 parts.

2. The inorganic coated cover tape according to claim 1, characterized in that: in, The aqueous silicon dioxide dispersion is a silica sol with a particle size of 5nm to 100nm. The wetting agent is di-2-ethylhexyl succinate sodium salt, The solubilizing agent is a water-soluble solvent, The silane coupling agent is one or more of silanes containing two, three or four alkoxy groups.

3. The inorganic coated cover tape according to claim 2, characterized in that: in, The aqueous silica dispersion is Guangdong Huihe SW-40 acidic silica sol, The wetting agent is HYDROPALAT WE 3475 from BASF. The solubilizing agent is ethanol, The silane coupling agent is KH-550 aminopropyl triethoxysilane and / or KH-560 3-glycidyloxypropyl trimethoxysilane.

4. The inorganic coated cover tape according to claim 1, characterized in that: in, The pH regulator is ammonia water with a concentration of 25%-28%.

5. The inorganic coated cover tape according to claim 1, characterized in that: in, The materials of the first self-adhesive layer and the second self-adhesive layer are both silane-modified butyl self-adhesive containing white oil and polyisobutylene, and the embryo layer is a PET film.

6. The inorganic coated cover tape according to claim 1, characterized in that: Also includes: Release layer, Wherein, the release layer and the second self-adhesive layer are bonded together.

7. The inorganic coated cover tape according to claim 6, characterized in that: in, The release layer is a release film or a release paper.

8. The inorganic coated cover tape according to claim 6, characterized in that: in, The release layer is double-sided release paper.

9. The inorganic coated cover tape according to claim 6, characterized in that: in, The thickness of the inorganic coating is 0.03mm-0.2mm, The thickness of the first self-adhesive layer is 0.1 mm-0.5 mm. The thickness of the embryo layer is 0.05mm-0.2mm. The thickness of the second self-adhesive layer is 0.1 mm to 0.5 mm. The thickness of the release layer is 0.01 mm-0.1 mm.

10. A method for preparing an inorganic coated cover tape, characterized in that: The following steps are involved: Step S1, adding an aqueous silica dispersion, a wetting agent, a solubilizer, and a silane coupling agent into a stirring kettle, stirring and dispersing them uniformly; then adding a pH regulator, and continuing stirring at room temperature for 0.5-1 hour to obtain a uniform emulsion dispersion, i.e., an aqueous inorganic coating, and discharging the material for later use; Step S2, preparing silane-modified butyl rubber according to Example 1 in CN113621343B; Step S3, feeding the silane-modified butyl rubber into an extruder, and extruding a 0.2 mm-0.4 mm butyl rubber layer on both sides of the PET embryo at one time through an extrusion die to obtain a first self-adhesive layer and a second self-adhesive layer, the extrusion temperature is set between 80-110° C., and the second self-adhesive layer is then composited with a double-sided release paper and rolled up to obtain a semi-finished product A; Step S4, introducing the water-based inorganic coating obtained in step S1 into the glue tank, coating it on the first self-adhesive layer through a glue roller, controlling the thickness of the dry glue to be 0.03mm-0.10mm, baking and drying in an oven, and rolling up to obtain a large roll of semi-finished product B, and finally rolling up the semi-finished product B through a slitting machine to obtain a finished small roll.

Citation Information

Patent Citations

  • Silane-modified self-adhesive butyl adhesive and waterproof membranes containing silane self-adhesive butyl adhesive

    CN113621343B

  • Polyurethane doped SBC hot melt adhesive and preparation method thereof

    CN117050698A